(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article explores the importance of musical art, particularly the musical heritage of Eastern scholars, in the development of professional competence among future directors. It examines how the musical legacy of such eminent figures as al-Farabi, Ibn Sina, Jami, Navoi, and Babur contributes to shaping the musical thinking of prospective directors.